(untitled) (Baghdad Science Journal, 2020)
Background: Adipose derived-mesenchymal stem cells have been used as an alternative to bone marrow cells in this study. Objective: We investigated the in vitro isolation, identification, and differentiation of stem cells into neuron cells, in order to produce neuron cells via cell culture, which would be useful in nerve injury treatment. Method: Mouse adipose mesenchymal stem cells were dissected from the abdominal subcutaneous region. Neural differentiation was induced using β-mercaptoethanol. This study included two different neural stage markers, i.e. nestin and neurofilament light-chain, to detect immature and mature neurons, respectively. Results: The immunocytochemistry results showed that the use of β-mercaptoethanol resulted in the successful production of neuron cells. This was attributable to the increase and significant overexpression of the nestin protein during the early exposure period, which resulted in the expression of the highest levels of nestin. In comparison, the expression level of neurofilament light-chain protein also increased with time but less than nestin. Non-treated mesenchymal stem cells, considered as control showed very low expression for both markers. Conclusion: The results of this study indicate that adipose mesenchymal cells represent a good, easily obtainable source of bone marrow cells used to developing the differentiation process.